PARALLEL COMPUTING IN THE HEAT AND MOISTURE TRANSFER USING SPS SOFTWARE - P. K. Shalkevich; S. P. Kundas; I. A. Gishkeluk (Informatika)
A numerical model of non-isothermal moisture transfer in soil is developed and adapted for used media. An SPS software module which allows carrying out long-term forecasting for the solution of three-dimensional non-isothermal heat and moisture transfer of contaminants in soil is developed.